Analisis Nilai Sosial dalam Iklan Gojek Edisi “Jangan Sepelekan Kekuatan Jempol” di Youtube - Wisnu Dwi Yuliyanto; Rahmawati Zulfiningrum (Departement of Mathematics Education, 2023)
The phenomenon of decreasing social values in the society, as depicted in the Gojek ad campaign